The effect of ankle bracing on lower extremity biomechanics during landing: A systematic review - Mason-Mackay, A. R.; Whatman, C.; Reid, D. (Journal of Science and Medicine in Sport, 2016)
Objectives: To examine the evidence for effect of ankle bracing on lower-extremity landing biomechanics. Design: Literature review. Methods: Systematic search of the literature on EBSCO health databases. Articles critiqued by two reviewers. Results: Ten studies were identified which investigated the effect of ankle bracing on landing biomechanics. Overall results suggest that landing biomechanics are altered with some brace types but studies disagree as to the particular variables affected. Conclusions: There is evidence that ankle bracing may alter lower-extremity landing biomechanics in a manner which predisposes athletes to injury. The focus of studies on specific biomechanical variables rather than biomechanical patterns, analysis of pooled data means in the presence of differing landing styles between participants, variation in landing-tasks investigated in different studies, and lack of studies investigating goal-directed sport-specific landing tasks creates difficulty in interpreting results. These areas require further research.